Working Capital in the Operations of Commercial Companies in Ecuador - de Jesús Luzuriaga Granda, Ignacia; Riofrío Leiva, Luis Antonio; González Vilela, Fanny Yolanda; Briceño Luzuriaga, Yesenia Alexandra (Journal of Applied Business and Economics, 2023)
The present study makes an analysis of the working capital of the companies in the commercial sector of Ecuador, in order to know how the working capital affects the economic results of commercial organizations during the year 2021. The research is descriptive, analytical and correlational, based on the database of the Superintendence of Companies (SC) and Insurance SC with a sample of the 40 largest companies according to their assets and applying multiple correlation to determine the relationships between working capital and other selected variables; Among the main results, it is highlighted that one of the components of working capital, current assets, has a direct correlation with total assets, that is, when the company invests the most, it does so in a large majority in resources that can be converted into cash in less than 12 months, with a significance of 0,67. The problem arises from the need to know how the working capital WC influences the obtaining of results at the end of a fiscal year, in one of the largest sectors in the country and that contributes significantly with jobs and taxes to the state; considering also that the largest companies in Ecuador belong to the sector, according to the Ranking of the control body, such as La Favorita Corporation that operates with an investment of $2.178.780.982,22; income tax of $57.787.752,77 and profit for the year 2021 of $232.280.036,22 in the last year reported to the SC.